PERBEDAAN PEMBERIAN LARUTAN VITAMIN B KOMPLEKS PADA TELUR TETAS TERHADAP HASIL TETAS AYAM KAMPUNG - Aprilianto Bayu Arisandy; Agustina Widyasworo; Eddy Trijana Sudani (AVES: Jurnal Ilmu Peternakan, 2018)
ABSTRACT The research was conducted at Mrs. Sripurwanti's farm in Rejotangan Village, Rejotangan Sub-district, Tulung Agung Regency. The research was conducted from 1 March to 1 April 2017. The aim of the research to determine the difference in the solution of Vitamin B Complex to the results of domestic chicken include hatchability, mortality and hatching weight. Research material using selected 225 eggs of chicken eggs and Vitamin B Complex as many as 30 grains. The research method used is experiments with Completely Randomized Design (RAL). The study was divided into 5 treatments and 5 replications per repeat consisting of 9 eggs. Treatment consists of the addition of Vitamin B complex as much as 0, 45 mg, 90 mg, 135 mg, and 180 mg The results are expected can provide information about alternative moisture enhancer ingredients namely Vitamin B Komplek. The results showed that vitamin B complex was not significant (P> 0.05) to hatchability, live eggs and die 2nd candling , mortality, and hatching weight. Vitamin B complex has significant effect (P <0,05) on hatchability and mortality based on candling to 2. Result of the research can be concluded that giving Vitamin B Complex as much as 45 mg deserves to be additive addition of humidity because it can increase the percentage of hatchability by 15%